Dual‐state and self‐oscillating wireless charging system topology for direct‐drive battery - Bo Li; Bao Zhang; Kai Xie (IET Power Electronics)
Abstract This study proposes a novel topology with bi‐stable controlling for wireless charging system (WCS). The advantage of the proposal is that a desired charging current can be directly output from rectifier without requiring charging current manager, thereby greatly simplifying the structure of the receiver. The proposed topology not only improves the transmission efficiency of system, but also reduces the loss and heat dissipation in the receiver. The principle of the topology is outlined and the circuitry model and control strategy are established and analyzed in detail. The innovation of this method lies in treating the coupler as a current transformer, which enables more direct and simpler controlling of the charging current. The experiment is conducted to verify that when the peak charging current is increased from 5A to 10A, the system efficiency is increased up to 82.0% and the receiver efficiency up to 96.7%. Both computational simulation and experimental validation have confirmed the feasibility of the proposed method. Compared with conventional WCS topology with compensation, the proposed method improves the system efficiency by 3% and the receiver efficiency by 5%, which is more suitable for practical applications where compact and light‐weight receiver is required.